Enhancing DNT Detection by a Bacterial Bioreporter: Directed Evolution of the Transcriptional Activator YhaJ - Elad, Tal; Shemer, Benjamin; Simanowitz, Shilat; Kabessa, Yossef; Mizrachi, Yosef; Gold, Azriel; Shpigel, Etai; Agranat, Aharon J.; Belkin, Shimshon (Frontiers in Bioengineering and Biotechnology, 2022)
Detection of buried landmines is a dangerous and complicated task that consumes large financial resources and poses significant risks to the personnel involved. A potential alternative to conventional detection methodologies is the use of microbial bioreporters, capable of emitting an optical signal upon exposure to explosives, thus revealing to a remote detector the location of buried explosive devices. We have previously reported the design, construction, and optimization of an Escherichia coli-based bioreporter for the detection of 2,4,6-trinitrotoluene (TNT) and its accompanying impurity 2,4-dinitrotoluene (DNT). Here we describe the further enhancement of this bioreporter by the directed evolution of YhaJ, the transcriptional activator of the yqjF gene promoter, the sensing element of the bioreporter’s molecular circuit. This process resulted in a 37-fold reduction of the detection threshold, as well as significant enhancements to signal intensity and response time, rendering this sensor strain more suitable for detecting the minute concentrations of DNT in the soil above buried landmines. The capability of this enhanced bioreporter to detect DNT buried in sand is demonstrated.